RETRACTED: The effect of using innovative technologies on the formation and development of competences of primary class students - Khayitov Umidjon; Qo’ldoshev Rustambek; Nurulloyev Firuz; Xalikova Umida (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001